Pengaruh Kompensasi, Pengembangan Karier dan Motivasi Kerja Terhadap Kinerja Karyawan - Nandafiriska, Ika; Marhandri, Dessy (Jurnal Ilmiah Ekotrans & Erudisi, 2021)
This study aims to ascertain the impact of salary, career growth, and job motivation on the performance of employees at PT. Indo Gemilang Sakti. This observational method is correlational, specifically including examining the relationship between two or more variables by extracting samples from a questionnaire. The samples are obtained using the Slovin formula, with a sample size of 80 out of 100 respondents. This study employs multiple linear regression analysis, hypothesis testing using the t-test method, the F-test, and the examination of the determinant coefficient. The findings of this study indicate that salary, career development, and job motivation have a favorable and significant impact on the performance of employees at PT. Indo Gemilang Sakti.